Uprising Of Village Democracy: Challenge And Opportunities For Village - James Reinaldo Rumpia (Bandar Lampung University, 2015)
Village always be integral part of Indonesia, and also their village democracy. Village Democracy became way of life in Indonesia even before independence. The concept of village democracy is seen in the form of deliberation, consensus, and mutual help. Either ungrateful or forgotten, Village democracy today is still isolated by regulation. The regulation that established always put the village as objects of development, not as a subject. The village democracy even in the New Order Era absolutely suppressed, through Law No. 5 of 1979 on village government. Thousand Village spread around Indonesia is required to equalize the structure, governments, even culture into Javanization concept. Village regulations in Reform Era are also not much dissimilar. The village was ordered as the executor of the rest of the tasks of the government. Village development is Top-Down and just based on mere government's desire, not on the ideas and desires of Village. The presence of Law No. 6 of 2014 on Village, changed the paradigm of village development. Village democracy being soul of villages development in Law No. 6 of 2014. The rise of democracy was also supported by extraordinary sources of funding. It is seen in Article 72 Law No. 6 of 2014 and Government Regulation No. 60 Year 2014. Opportunities to realized village democracy and access the funds have many requirements. Village must making RPJMDes, APBDes, and various legal instrument in the form of PeraturanDesa. This condition is certainly a challenge for Village, to be ready in human resources, institutions, and civil society.